Optimizing of Turbine blade spar using Ansys program - Al-Maliky, Firas Thair; Kadhim, Dhurgham A. (Journal of Petroleum Research and Studies, 2022)
The current work involved optimizing the spars of wind turbine blades while taking into account the wind speed quantities that affected the blade structure. The objective was to determine the optimal dimensions of turbine blade spar configurations using the finite element method under the influence of the maximum pressure associated with the first mode shape while maintaining the Von Misses stresses within the assumed safety factor (1.5). (200-230 MPa). The blade was stiffened with a main box spar and two auxillary spars on each side. Appropriate spar locations were specified for poisons with a high natural frequency first mode. The blade parts’ dimensions were discretized to allow for greater flexibility and precision in dimension assignment. By utilizing the ANSYS program, the optimization process required a certain number of iterations to modify the blade structure’s dimensions. Optimized iteration was considered in order to increase the thickness in areas of high stress and decrease the thickness in areas of low stress. Additionally, a comparison between a blade structure with optimal dimensions and one with non-optimal dimensions was included.